A Compact Passive Quad‐Band Negative Group Delay Circuit With Stepped Impedance Resonator and Defected Microstrip Structure. Issue 1 (10th January 2023) - Zhang, Li; Yang, Shuhui; Guo, Qingxin; Xiao, Huaibao; Wang, Ling; Li, Bin; Zhang, Hui
Abstract: Based on two‐stage stepped impedance resonator (SIR) and defected microstrip structure (DMS) with an E‐shaped slot, a novel compact passive quad‐band negative group delay circuit (NGDC) is proposed whose resonation frequencies and group delay performance are mainly determined by the SIR and the DMS. In order to help reveal the working mechanism of the quad‐band NGDC, an equivalent circuit of the NGDC is developed. It is composed of the transmission lines and serial‐parallel LC networks, and its S‐ parameters are derived by using the theory of transmission matrix. The theoretical and simulated results for the transmission characteristics of the NGDC agree well with each other. To validate the design concept, a prototype of the proposed quad‐band NGDC was fabricated and measured. The measured results show that at the frequencies of 2.64, 7.88, 13.08, and 18.18 GHz, the negative group delay values achieve −5.4, −3.1, −1.18, and −1.14 ns, with | S 21 | values of −17.2, −20.5, −12.8, and −18.1 dB, respectively. Compared with the recently reported works, the proposed NGDC exhibits the largest number of operation frequency bands. Furthermore, it does not use lumped resistors and has miniaturized dimension. Key Points: It proposes a quad‐band negative group delay circuit (NGDC) using stepped impedance resonator and an E‐shaped slot defected microstrip structure An equivalent circuit of the NGDC is developed to help reveal the working mechanism At the frequencies of 2.64, 7.88, 13.08, and 18.18 GHz, the negative group delay values achieve −5.4, −3.1, −1.18, and −1.14 ns, respectively